Observation of adverse effect on level ammonia through expression of CD8 lymphocyte in mice - Tualeka, Abdul Rohim; Jalaludin, Juliana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: The production of ammonia has been increasing over the past few years. Unfortunately, the production does not follow the safety control of ammonia on workers. Indonesia still adopts chemical standard from other countries. Therefore, it requires an ammonia standard at the highest dose without effect or no observed adverse effect level (NOAEL) in the workplace. This research aims to determine standard at the highest dose of without effect through the expression of CD8 cells as well as analysis of histological alteration CD8 lymphocyte between exposed to ammonia group and control. Methods: The study was a laboratory experimental research with a post-test only control group design. The research used Rattus novergicus species as many as 24. NOAEL was determined by middle dose with a location between the smallest and the largest dose. The doses of ammonia were given through inhalation. The histological alteration of CD8 between ammonia in exposed and the control group were analyzed by using the Kruskal Wallis test. Results: NOAEL was found through CD8 located in group 3 with 0.0154 dose mg/kg body weight. There was a differential expression of CD8 lymphocyte cells in the white mice lung between exposed to ammonia group and control (p=0.042). Conclusion: The expression of CD8 lymphocyte cells in the white mice lung exposed to ammonia differs significantly with the number of the expression of CD8 lymphocyte cells in white mice lung at control group. NOAEL was 0.0154 mg/kg body weight of white mice.